Rational Design of Conjugated Photosensitizers with Controllable Photoconversion for Dually Cooperative Phototherapy. Issue 29 (3rd June 2018) - Ye, Shuyue; Rao, Jiaming; Qiu, Shihong; Zhao, Jinglong; He, Hui; Yan, Ziling; Yang, Tao; Deng, Yibin; Ke, Hengte; Yang, Hong; Zhao, Yuliang; Guo, Zhengqing; et al.
Abstract: High‐performance photosensitizers are highly desired for achieving selective tumor photoablation in the field of precise cancer therapy. However, photosensitizers frequently suffer from limited tumor suppression or unavoidable tumor regrowth due to the presence of residual tumor cells surviving in phototherapy. A major challenge still remains in exploring an efficient approach to promote dramatic photoconversions of photosensitizers for maximizing the anticancer efficiency. Here, a rational design of boron dipyrromethene (BDP)‐based conjugated photosensitizers (CPs) that can induce dually cooperative phototherapy upon light exposure is demonstrated. The conjugated coupling of BDP monomers into dimeric BDP ( di ‐BDP) or trimeric BDP ( tri ‐BDP) induces photoconversions from fluorescence to singlet‐to‐triplet or nonradiative transitions, together with distinctly redshifted absorption into the near‐infrared region. In particular, tri ‐BDP within nanoparticles shows preferable conversions into both primary thermal effect and minor singlet oxygen upon near‐infrared light exposure, dramatically achieving tumor photoablation without any regrowth through their cooperative anticancer efficiency caused by their dominant late apoptosis and moderate early apoptosis. This rational design of CPs can serve as a valuable paradigm for cooperative cancer phototherapy in precision medicine. Abstract : The rational design of boron‐dipyrromethene‐based conjugated photosensitizers within nanoparticles is reported. These systems can induce dually cooperative phototherapy through controllable photoconversions for achieving tumor photoablation surgery upon NIR light exposure.